A comparative study of the compliments and compliment responses between English and Persian TV interviews - Biook Behnam,; Niloufar Amizadeh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper is a cross-cultural study of compliments and compliment responses in American and Persian TV interviews. Based on eight video-taped and transcribed interviews of Oprah Winfrey’s programs with celebrities from MBC4 channel and eight Persian interviews conducted by the Iranian TV host Reza Rashid Pour with eight Iranian celebrities, the paper investigated the topic and the function of the compliments and the way interlocutors responded to the compliments in the Persian and American TV interviews. The project set out to examine the similarities and differences in the compliments and compliment responses of English and Persian TV interviews. The result of our analysis revealed that there are both similarities and differences between the complimenting behavior of English and Persian interlocutors when complimenting and responding to compliments in TV interviews. This study lends weight to the claim that complimenting behavior is cross-culturally varied and different.